PENGARUH WORK ENVIRONMENT, STRES KERJA, DAN DUKUNGAN KELUARGA YANG DIMEDIASI OLEH DUKUNGAN KELUARGA TERHADAP KINERJA UMKM: (STUDI KASUS PADA UMKM KECAMATAN PEDURUNGAN) - Qudrotul Ainiyah, Lissa; Qristin Violinda; Noni Setyorini (JURNAL BISNIS KOLEGA, 2023)
The Influence of Work Environment, Job Stress and Business Management Mediated by Family Support on the Performance of MSMEs in Pedurungan District" (Case Study of MSMEs in Pedurungan District). PGRI University Semarang Management Study Program 2023. This research uses a probability sampling technique with the Cluster Random Sampling method as a sample determination technique. The data analysis process uses the Structural Equation Model Partial Least Square (SEMPLS) analysis model with the help of the SmartPLS 3.0 analysis tool. The population used in this research were MSME owners located in Pedurungan District and the sample used was 350 respondents. Primary data by distributing questionnaires via Google Form. The results of the analysis and discussion show that there is a positive and significant influence between the Work Environment variable (X1) which is mediated by Family Support (Z) on the MSME Performance variable (Y) in partial terms, with a t-statistic of 2.127 and a p-value of 0.034 < 0.05. There is a positive and significant influence between the Work Stress variable (X2) which is mediated by Family Support (Z) on the MSME Performance variable (Y) in part, with a t-statistic of 2.185 and a p-value of 0.029 < 0.05. There is a significant influence between the Business Management variable mediated by Family Support (Z) on the MSME Performance variable (Y) in partial terms, with a t-statistic of 2.067 and a p-value of 0.009 < 0.05